Thioredoxin‐interacting protein (TXNIP) is a substrate of the NEDD4‐like E3 ubiquitin‐protein ligase WWP1 in cellular redox state regulation of acute myeloid leukemia cells - Sara Giovannini; Yanan Li; Rosalba Pecorari; Claudia Fierro; Claudia Fiorilli; Federica Corigliano; Valeria Moriconi; Ji Zhou; Anna De Antoni; Artem Smirnov; Sara Rinalducci; Anna Maria Timperio; et al. (Molecular Oncology)
The HECT‐type E3 ubiquitin WWP1 (also known as NEDD4‐like E3 ubiquitin‐protein ligase WWP1) acts as an oncogenic factor in acute myeloid leukemia (AML) cells. WWP1 overexpression in AML confers a proliferative advantage to leukemic blasts (abnormal immature white blood cells) and counteracts apoptotic cell death and differentiation. In an effort to elucidate the molecular basis of WWP1 oncogenic activities, we identified WWP1 as a previously unknown negative regulator of thioredoxin‐interacting protein (TXNIP)‐mediated reactive oxygen species (ROS) production in AML cells. TXNIP inhibits the disulfide reductase enzymatic activity of thioredoxin (Trx), impairing its antioxidant function and, ultimately, leading to the disruption of cellular redox homeostasis. In addition, TXNIP restricts cell growth and survival by blocking glucose uptake and metabolism. Here, we found that WWP1 directly interacts with TXNIP, thus promoting its ubiquitin‐dependent proteasomal proteolysis. As a result, accumulation of TXNIP in response to WWP1 inactivation in AML blasts reduces Trx activity and increases ROS production, hence inducing cellular oxidative stress. Increased ROS generation in WWP1‐depleted cells culminates in DNA strand breaks and subsequent apoptosis. Coherently with TXNIP stabilization following WWP1 inactivation, we also observed an impairment of both glucose up‐take and consumption. Hence, a contribution to the increased cell death observed in WWP1‐depleted cells also possibly arises from the attenuation of glucose up‐take and glycolytic flux resulting from TXNIP accumulation. Future studies are needed to establish whether TXNIP‐dependent deregulation of redox homeostasis in WWP1‐overexpressing blasts may affect the response of leukemic cells to chemotherapeutic drugs.